Railway Bridge Design Analysis With Deck Bulb Tee WF98DG Type Bearer Using Bridgelink V.8.0.0.2 - efendi, aco; Safitri, Novia (SAINSTECH NUSANTARA, 2024)
The railroad track is crucial for people to cross the train, especially on lines with quite high elevations where the railroad is not permitted to have particularly high gridlines on its tracks. In its literal sense, a bridge is a construction that connects two areas that are divided by a barrier, which can be man-made or natural, such as highways, irrigation canals, and railroads, or it can be a river, valley, strait, or sea. The researcher will model the bridge girder with Bridgelink software for tracks on public railways, using pre-stressed concrete material with the type of grinder is Deck Bulb Tee WF98DG with a bridge span of 30 m. Referring to the railway geometry planning parameters according to the Minister of Transportation regulation No. PM. 60 of 2012. From the results of this study it is known that with a bridge cross-section of 3.124 m wide according to the needs of the width of the cross-section of a one-lane railway, which is a minimum of 3 m with a span length of 30 m using a single axle load of 20 tons requires a girder cross-section type Deck Bulb Tee WF98DG with the number of straight strand recommendations from bridge link is 18 pieces and Harped Strand as many as 7 pieces using fc' 35.16 MPa.